Gvscapes: mobilising the scavenger hunt for english language learning - Esther Jawing; Siti Hasnah Tanalol; Siti Nur Farah Mohammad Saleh (Solid State Technology, 2020)
When the world is at our fingertips, the new generation of students appear to be more technology driven towards electronic devices usage in their daily life. The smartphones and smart electronic devices are fast improving with the advancement of the new generation of android devices. In addition, some devices are built specifically for Augmented Reality (AR). The 21st century learning approach advocates the integration of technology for more interactive teaching and learning activities. Thus, this research had developed a mobile AR application which integrated the android-based application to assist the teaching and learning activities in University Malaysia Sabah (UMS). UMS students are obligatory to take the English language courses from the Centre for the Promotion of Knowledge and Language Learning (CPKLL). However, the current challenges in the English language classrooms are students’ lack of interest in conventional teaching and learning activities as well as limited attention span during lessons. In view of this, the gamification element is injected inside the classroom by utilising a creative method to the existing conventional scavenger hunt game. The implementation of an android application with AR aptitude allows the students to play educational quizzes. The two-fold objectives of this project included: (1) developing an android-based fun quiz application with AR technology which was location-based so students could experience interactive learning environment; and (2) investigating the implementation of this mobile application during English lessons. Iterative methodology was employed in this research which comprised planning, analysis, design, implementation, testing phase, deployment and follows next iteration (if needed). The findings suggested that students were able to answer the AR quizzes at several locations around UMS and provided the lecturers with real time access to the results. However, there were some identified disadvantages such as safety hazards and contents. It is hoped that GVScapes will provide more interactive and learning activities via gamification.